Practical measurement of body composition using bioelectrical impedance, air displacement plethysmography and ultrasound in stable outpatients with short bowel syndrome receiving home parenteral nutrition: comparison of agreement between the methods. Issue 3 (22nd November 2018) - Jones, D. J.; Lal, S.; Gittins, M.; Strauss, B. J. G.; Burden, S. T.
Abstract: Background: People diagnosed with intestinal failure (IF) as a result of short bowel syndrome are dependent on home parenteral nutrition (HPN). Measuring nutritional status is essential for monitoring treatment. The present study aimed to determine the agreement and feasibility of three methods bioelectrical impedance analysis (BIA), ultrasound and air displacement plethysmography (ADP) for measuring body composition in people receiving HPN. Methods: Body composition data were collected from patients attending an IF clinic. Results: There were 50 participants recruited and data were collected for BIA ( n = 46), ultrasound ( n = 49) and ADP ( n = 9). Numbers for ADP were much lower because of a lack of participant uptake. Fat‐free mass (FFM) measured by BIA and ultrasound in comparison to ADP was found to have good intraclass correlation (ICC) 0.791 (95% confidence interval (CI) CI −0.21 to 0.96) and a moderate ICC 0.659 [95% (CI) −0.27 to 0.92], respectively. Fat mass (FM) measured by both BIA and ultrasound in comparison to ADP was found to have moderate ICC 0.660 (95% CI −0.28 to 0.92) and poor ICC −0.005 (95% CI −0.73 to 0.65), respectively. Conclusions: Compared to ADP, BIA indicated moderate to good agreement for measuring body composition, whereas ultrasound indicated far less agreement, particularly when measuring FM. The lack of uptake of ADP suggests that participants found the Bodpod (COSMED Srl, Shepperton, UK) unfavourable. Considering that ultrasound has limited agreement and ADP was not the preferred option for participants, BIA shows some potential. However, the difference between ADP and BIA was larger for FM compared to FFM, which needs to be considered in the clinical setting.